2011
DOI: 10.1038/jid.2010.350
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Confirms the LCE3C_LCE3B Deletion as a Risk Factor for Psoriasis in Several Ethnic Groups and Finds Interaction with HLA-Cw6

Abstract: A multicenter meta-analysis including data from 9389 psoriasis patients and 9477 control subjects was performed to investigate the contribution of the deletion of genes LCE3C and LCE3B, involved in skin barrier defense, to psoriasis susceptibility in different populations. The study confirms that the deletion of LCE3C and LCE3B is a common genetic factor for susceptibility to psoriasis in European populations [OROverall = 1.21 (1.15–1.27)], and for the first time directly demonstrated the deletion's associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
92
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 15 publications
8
92
2
5
Order By: Relevance
“…Previous studies showed a genetic interaction between LCE3C_LCE3B-del and HLA-C*06 in populations from the Netherlands, USA and China (10)(11)(12). In addition, epistasis between PSORS1 and PSORS4 loci has been reported in an Italian cohort (13).…”
Section: Questions Addressedmentioning
confidence: 99%
“…Previous studies showed a genetic interaction between LCE3C_LCE3B-del and HLA-C*06 in populations from the Netherlands, USA and China (10)(11)(12). In addition, epistasis between PSORS1 and PSORS4 loci has been reported in an Italian cohort (13).…”
Section: Questions Addressedmentioning
confidence: 99%
“…Heterozygous or homozygous deletion of LCE3B and LCE3C, which is observed in greater than 90% of patients with psoriasis, could potentially affect skin barrier properties (compared with the homozygous ancestral status of two intact chromosomes), in particular under conditions of stress. 7 Thus, concerning the relevance for psoriasis, there is deletion of two of five LCE3 genes rather than two of 18 LCE genes. Because LCE3B and LCE3C are expressed at low levels, if at all, in normal skin, the situation is different from the filaggrin (FLG) gene and atopic dermatitis.…”
mentioning
confidence: 99%
“…Its reported epistasis with HLA-Cw6 in at least some white populations makes it a major risk factor for psoriasis. 7 Inasmuch as all LCE genes are similar and would be predicted to exert similar functions, the question arises as to why deletion of 2 of 18 quite similar LCE genes could have a role in the etiology of psoriasis. Herein it was demonstrated that four of the five LCE3 genes are differently expressed compared with other LCE groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,[8][9][10] But what stands out is that all patients with ISL had at least one copy of the LCE3C LCE3B deleted alleles (absence of nondeleted homozygous individuals). In the general population, the frequency of non-deleted homozygotes is around 18% 4,9,10 and disruption of the skin barrier occurs in relation to the number of copies of LCE3C LCE3B, being undetectable in carriers of the homozygous deletion 4 and reduced in heterozygotes.…”
mentioning
confidence: 99%